Islamic finance and economic growth in Indonesia: Analyzing short-and long-term effects - Muhamad Nisar; Gustriani; Ichsan Hamidi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This research examines the impact of Islamic finance on Indonesia’s economic growth. Using quarterly time series data on Islamic banking, Islamic mutual funds, Islamic pawnshops, Zakat, Infaq, and Shadaqah (ZIS) from 2014 to 2022 (36 observations), and applying the Error Correction Model (ECM), the study evaluates both short- and long-term effects. The results show that, in the short term, only Islamic banking financing has a significant positive effect, while Islamic mutual funds, Islamic pawnshops, and ZIS are not significant. In the long term, Islamic banking, Islamic pawnshops, and ZIS contribute positively and significantly to economic growth. These findings support financial intermediation and Islamic social finance theory, indicating that Islamic financial institutions channel funds into the economy, with effects that vary over time. They also highlight the role of Islamic finance in promoting financial inclusion, supporting micro and small enterprises, and improving welfare through income redistribution. This study suggests that policymakers should reinforce the regulatory framework for Islamic finance. Despite its lack of short-term significance, their long-term benefits underscore the necessity for policies to facilitate their growth and integration into the broader financial system.